1997
DOI: 10.1523/jneurosci.17-07-02469.1997
|View full text |Cite
|
Sign up to set email alerts
|

NR2A Subunit Expression Shortens NMDA Receptor Synaptic Currents in Developing Neocortex

Abstract: NMDA receptors play important roles in learning and memory and in sculpting neural connections during development. After the period of peak cortical plasticity, NMDA receptor-mediated EPSCs (NMDAR EPSCs) decrease in duration. A likely mechanism for this change in NMDA receptor properties is the molecular alteration of NMDA receptor structure by regulation of NMDA receptor subunit gene expression. The four modulatory NMDAR2A-D (NR2A-D) NMDA receptor subunits are known to alter NMDA receptor properties, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
404
4
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(447 citation statements)
references
References 35 publications
37
404
4
2
Order By: Relevance
“…Previous studies demonstrated that dark rearing or 5 d of visual deprivation in juvenile rats decreases the relative expression of NR2A-to NR2B-containing NMDARs, resulting in longer NMDAR-mediated currents (Carmignoto and Vicini, 1992;Flint et al, 1997;Philpot et al, 2001a). We found that a similar process occurs in mice.…”
Section: Visual Deprivation Lengthens the Decay Kinetics Of Synaptic supporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies demonstrated that dark rearing or 5 d of visual deprivation in juvenile rats decreases the relative expression of NR2A-to NR2B-containing NMDARs, resulting in longer NMDAR-mediated currents (Carmignoto and Vicini, 1992;Flint et al, 1997;Philpot et al, 2001a). We found that a similar process occurs in mice.…”
Section: Visual Deprivation Lengthens the Decay Kinetics Of Synaptic supporting
confidence: 70%
“…NR1, NR2A, and NR2B subunits predominate in the postnatal visual cortex, and during development the ratio of NR2A-to NR2B-containing NMDARs increases (Quinlan et al, 1999a,b;Roberts and Ramoa, 1999). Because NR2A-containing NMDARs possess shorter current durations than NR2B-containing receptors, NMDAR-mediated current durations shorten over development (Carmignoto and Vicini, 1992;Hestrin, 1992;Monyer et al, 1992;Priestley et al, 1995;Flint et al, 1997;Vicini et al, 1998). The developmental increase in NR2A in the visual cortex is experience-dependent, because dark rearing delays the increase in NR2A in the visual cortex (Nase et al, 1999;Quinlan et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…The delayed maturation of postsynaptic G protein mediated GABA B inhibition also contributes to increased brain excitability [21]. The prolonged NMDA-mediated excitatory postsynaptic currents (EPSCs) in immature versus adult neurons will also promote the generation of network driven events [22].…”
Section: Partial Seizuresmentioning
confidence: 99%
“…For instance, in rat visual cortex, the duration of the NMDA-mediated EPSC decreases during development, and dark-rearing prevents this decrease (Carmignoto and Vicini, 1992). This decrease could be caused by a shift in NMDA receptor subunit expression (Sheng et al, 1994;Flint et al, 1997). Another possibility, not mutually exclusive, is that the levels of NMDA receptors themselves change during development in association with periods of cortical plasticity.…”
Section: Abstract: Nmdar1; Activity-dependent; Visual Cortex; Develomentioning
confidence: 99%
“…Our results suggest that the physiological alterations that occur during darkrearing do not result from major changes in the amount of NMDAR1 protein. However, NMDA receptor subunit composition (Sheng et al, 1994;Flint et al, 1997) and/or phosphorylation state (Roche et al, 1994;Tingley et al, 1997) may change with dark-rearing, because both have also been shown to affect channel function.…”
Section: Regulation Of Nmdar1 Immunoreactivity By Vision and Activitymentioning
confidence: 99%